2010
DOI: 10.1126/science.1192044
|View full text |Cite
|
Sign up to set email alerts
|

Ion-Mediated Electron Transfer in a Supramolecular Donor-Acceptor Ensemble

Abstract: Ion binding often mediates electron transfer in biological systems as a cofactor strategy, either as a promoter or as an inhibitor. However, it has rarely, if ever, been exploited for that purpose in synthetic host-guest assemblies. We report here that strong binding of specific anions (chloride, bromide, and methylsulfate but not tetrafluoroborate or hexafluorophosphate) to a tetrathiafulvalene calix[4]pyrrole (TTF-C4P) donor enforces a host conformation that favors electron transfer to a bisimidazolium quino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
147
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 158 publications
(153 citation statements)
references
References 22 publications
4
147
1
Order By: Relevance
“…), thermal and photoinduced transformations of organic compounds [1][2][3]. To date, a detailed study of the photoinduced electron transfer processes (PET) has been made, in particular, the effect of factors such as the electronic structure of the donor and the acceptor, the polarity of the medium, and the excitation energy [4].…”
Section: Introductionmentioning
confidence: 99%
“…), thermal and photoinduced transformations of organic compounds [1][2][3]. To date, a detailed study of the photoinduced electron transfer processes (PET) has been made, in particular, the effect of factors such as the electronic structure of the donor and the acceptor, the polarity of the medium, and the excitation energy [4].…”
Section: Introductionmentioning
confidence: 99%
“…As detailed below, we found that by using a mixture of the electron donating tetrathiafulvalene-appended calix [4]pyrrole (TTF-C4P) 21 with the dicationic electron acceptor bisimidazolium quinone (BIQ 2+ ) 22 we could reversibly switch the direction of electron transfer by varying the surrounding ionic environment. 23 Calix [4]pyrroles (C4P), in general, are a class of fluxional tetrapyrrolic macrocycles that bind selected anionic guests in organic solvents. 4c,24 Upon anion complexation, a change in the conformation of the C4P macrocycle occurs, converting it from the so-called 1,3-alternate to the corresponding cone conformation.…”
Section: Biological Systemsmentioning
confidence: 99%
“…Such reactions have subsequently been termed metal-ioncoupled (or -ion-mediated) electron transfer. [49,50] The electron transfer rates from the donor are accelerated due to complexation of a redox-inactive metal with the radical anion of the substrate, significantly reducing the redox potential of the latter.…”
Section: Feedback Non-linearitymentioning
confidence: 99%